Estrés, Depresión Y Consumo De Alcohol En Estudiantes De Bachillerato De México: Diferencias Por Sexo Y Escuela - Almendra, Rosa Vargas; Arreola, Arturo del Castillo; Saldaña, Rebeca María Elena Guzmán (European Scientific Journal, ESJ, 2016)
Stress in teenagers studying high school is a health problem of great importance as not only affects behavior but also affects physical and mental health of this population, increasing the likelihood of depression occur and use alcohol as a means of coping with it. Objective: To determine the interaction by sex and type of school, as well as the relationship between levels of stress, depression and alcohol of high school students in two states in Mexico. Material and Methods: 129 students from two high schools in the states of Hidalgo and Mexico respectively selected through a non-probability sampling. The age range was from 16 to 21, M = 17 years, SD = .893. 51.2% were men and 48.8% women. Perceived Stress Scale (EEP) was used, the Beck Depression Inventory and Identification Questionnaire disorders due to alcohol consumption (AUDIT). They were conducted descriptive analyzes, Pearson correlation analysis and factorial ANOVA 2x2. Results: Significant negative relationships between stress and depression (r = .552, p <0.05) were found, also significant differences by gender in alcohol F (3,70) = 3.283, p ≤ .05 and significant differences by school in depression variable F (3,125) = 3.690, ≤ .05. Conclusion: These results provide insight into the association between different risk facotres student population so that from it culturally relevant psychological interventions that affect the prevention of health problems in this population are designed.